2016
DOI: 10.3109/07435800.2016.1156124
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic thiol/disulfide homeostasis in patients with autoimmune subclinical hypothyroidism

Abstract: We found that thiol/disulfide homeostasis shifted to disulfide formation in patients with subclinical hypothyroidism and that thyroid autoantibodies were positively correlated with thiol oxidation. It is not clear whether abnormal thiol/disulfide homeostasis is a cause or a consequence in Hashimoto thyroiditis. Further studies are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 21 publications
0
20
0
1
Order By: Relevance
“…Thiol/disulfit homeostazı (TDH) anti-oksidan korunma, detoksifikasyon, hücre büyümesi ve aopopitozu gibi birçok hücresel aktivitede kritik role sahiptir (10,11) . Daha önceleri prediabet, otoimmün subklinik hipotiroidizm (Hashimoto tiroiditi), polikistik over sendromu, Kırım Kongo hemorajik ateşi, ani sensorinöral işitme kaybı, prematür ovariyan yetmezlik gibi birçak farklı hastalıkta TDH'nın etyopatogenetik rolü araştırılmıştır (12)(13)(14)(15) . Bu homeostazın immün etyopatogenezde çok önemli rol oynadığı ve TDH'ındaki dengesizliğin oksidatif stres ve doku inflamasyonu aracılığıyla hastalığı tetiklediği düşünülmektedir.…”
Section: Introductionunclassified
“…Thiol/disulfit homeostazı (TDH) anti-oksidan korunma, detoksifikasyon, hücre büyümesi ve aopopitozu gibi birçok hücresel aktivitede kritik role sahiptir (10,11) . Daha önceleri prediabet, otoimmün subklinik hipotiroidizm (Hashimoto tiroiditi), polikistik over sendromu, Kırım Kongo hemorajik ateşi, ani sensorinöral işitme kaybı, prematür ovariyan yetmezlik gibi birçak farklı hastalıkta TDH'nın etyopatogenetik rolü araştırılmıştır (12)(13)(14)(15) . Bu homeostazın immün etyopatogenezde çok önemli rol oynadığı ve TDH'ındaki dengesizliğin oksidatif stres ve doku inflamasyonu aracılığıyla hastalığı tetiklediği düşünülmektedir.…”
Section: Introductionunclassified
“…Previous studies reported increased OS in adult patients with SHT [11-13]; these studies either included only patients with autoimmune hypothyroidism [11-13] or the presence of autoimmune thyroiditis was not reported [20, 21]. Hashimoto thyroiditis is a chronic inflammatory auto­immune disease.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal thiol/disulphide homeostasis plays a pivotal role in the pathophysiology of many chronic inflammatory diseases [14-16]. Increased OS may be related to autoimmunity in patients with Hashimoto thyroiditis [11]. The objective of this study was to evaluate dynamic thiol/disulphide homeostasis in children and adolescents with non-autoimmune SHT.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations